A Nationwide Cross-Sectional Survey of UK Breast Surgeons' Views on the Management of Ductal Carcinoma In Situ. (30th November 2015) - Mannu, Gurdeep S.; Bettencourt-Silva, Joao H.; Ahmed, Farid; Cunnick, Giles
Abstract : Background . There is wide variation in the management of Ductal Carcinoma In Situ (DCIS) nationwide. We aimed to investigate whether the attitudes of surgeons towards different aspects of DCIS treatment varied by seniority of surgeon or by geographical region within the UK. Materials and Methods . A nationwide online survey targeted at UK breast surgeons was undertaken. The anonymous survey contained questions regarding demographics of respondents and specific questions regarding DCIS management that were identified as areas of uncertainty during a systematic search of the literature. Results . Responses from 80 surgeons were obtained. Approximately 57% were male and the majority were consultant or specialist registrar. Approximately 63% of participants were based in district general hospitals with all training deaneries represented. Surgeons' views on the prognosis and management of DCIS varied geographically across the UK and terminology for DCIS varied with surgeon seniority. Surgeons' views particularly differed from national guidance on indications for SLNB, tamoxifen, and follow-up practice. Conclusion . Our survey reaffirms that, irrespective of national guidelines and attempts at uniformity, there continues to be a wide variety of views amongst breast surgeons regarding the ideal management of DCIS. However, by quantifying this variation, it may be possible to take it into account when examining long-term trends in nationwide treatment data.